TECHNOLOGICAL INNOVATION IN ENTREPRENEURSHIPS: AN ANALYSIS IN CIUDAD DEL ESTE Y PRESIDENTE FRANCO, PARAGUAY - Cañete Britez, Walter (Revista Gênero e Interdisciplinaridade, 2023)
The research on "Innovation and Technology in Entrepreneurship in Ciudad del Este and Presidente Franco - Paraguay" provides a deep insight into the current state of the entrepreneurial ecosystem in the region. The level of integration of innovative technologies, access to advanced tools, technological adoption patterns and available training resources were evaluated. The diversity in entrepreneurial motivations was highlighted, from the search for work independence to the identification of market opportunities. The results underline the importance of specific training programs to meet current technological demands. The promotion of strategic alliances, the creation of an innovation hub and the implementation of government incentives to support technological ventures is proposed. The relevance of digital marketing and the importance attributed to sustainability and social responsibility are highlighted. In summary, the research highlights the need for strategic actions to strengthen the entrepreneurial ecosystem, foster collaboration, and fully leverage the potential of innovation and technology in Ciudad del Este and Presidente Franco. These proposals seek to promote the sustainable growth of local enterprises and position the region as a center of innovation in Paraguay.